Hybrid Hydrogels Based on insitu Interpenetrating Networks Graphene Oxide (GO) and Au Nanoparticles, and Its Application as Peroxidase Mimetics for Glucose Detection. Issue 36 (27th September 2018) - Song, Dandan; Yang, Yuyan; Zhou, Tong; Liu, Yang; Song, Shasha; Zhang, Juan; Lu, Hongsheng; Zhao, Zengdian
Abstract: Graphene oxide (GO ) and Au Nanoparticles (NPs) hybrid hydrogels were prepared through one‐step hydrothermal method. The microstructure of GO/AuNPs hydrogels determined by SEM demonstrated that the hydrogels displayed three‐dimensional (3D) network structure. The freeze‐dried GO/AuNPs hydrogels (xerogels), i. e., GO/Au nanocomposites, could efficiently catalyze the oxidation reaction of peroxidase substrate, 3, 3′, 5, 5′‐tetramethylbenzidine (TMB), in the presence of H2 O2 to produce a blue color reaction. Compared with the natural enzyme, horse radish peroxidase (HRP), GO/Au nanocomposites exhibited higher peroxidase‐like activity. The reason might be that the porous 3D network structure of GO/Au nanocomposite enhanced the reaction activity. The catalytic reaction mechanism of GO/Au nanocomposite was followed the Michaelis‐Menten behavior. The combination of GO/Au nanocomposite with glucose oxidase (GOx) performed a selective colorimetric assay for glucose detection with a detection limit of 0.4728 μmol⋅L −1, which can be used as a promising candidate biosensor for glucose detection. Abstract : GO/Au nanocomposites can be obtained by freeze‐dried GO/AuNPs hybrid hydrogels, which could efficiently catalyze the oxidation reaction of peroxidase substrate, 3, 3′, 5, 5′‐tetramethylbenzidine (TMB), in the presence of H2 O2 to produce a blue color reaction. The catalytic reaction mechanism of GO/Au nanocomposite was followed the Michaelis‐Menten behavior. The combination of GO/Au nanocomposite with glucose oxidase (GOx) performed a selective colorimetric assay for glucose detection.